A "lenda" ou história da borboleta: os movimentos sociais e a educação - o caso do Movimento dos Trabalhadores Rurais Sem-Terra e a educação do campo - Ana Maria Alvarenga; António Teodoro (EccoS – Revista Científica)
The purpose of this study is to analyze the action of the landless workers´ movement (MST) in the reconstruction of education in Brazil in the current situation of crisis in formal education. The MST is presented as a dynamic social movement that has been constantly reinvented. Its claims and actions are based in the struggle for better life and work conditions and identity issues, and in opposition to neoliberal globalization as well. The movement has rebuilt the tradition of popular edu cation in Brazil, based on ideas of Paulo Freire. It has influenced the changes in public policies for education in rural areas. As a result, it is verified how essential is the participation of social movements in the construction of public policies for education, fostering and building an action of participatory democracy. In the "new" form to live the school experience and to (re) think its operation, the MST presents clues of an emancipator response to the current crisis of education.